(untitled) (Research, Society and Development, 2019)
Estimates of the progressive expansion of Alzheimer’s disease (AD) worldwide indicate the need for constant studies on this pathology, still without cure. Studies have investigated AD in non-human animal models using substances that induced AD. The present study aimed to review the literature on the substances and procedures used in laboratory to reproduce AD in rats. We selected 44 of 111 studies analyzed, keeping only papers that induced AD by chemical substances. The identified substances were aluminum, beta-amyloid, colchicine, d-galactose, scopolamine, streptozocin and homocysteine. It was verified that of the 44 articles, the most used substance was beta-amyloid, the main biomarker of AD. Although different studies have replicated results that simulate the occurrence of AD in rats and the treatments performed with rats in the laboratory appear promising, no cure has yet been found.